2020
DOI: 10.1016/j.injury.2020.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Missed hand and forearm injuries in multiple trauma patients: An analysis from the TraumaRegister DGU®

Abstract: Multiple trauma patients have a high risk of missed injuries. The main point of our study was to provide new epidemiological data on hand and forearm injuries in multiple trauma with a focus on those that were missed. Therefore, we used the database of the TraumaRegister DGU®.Methods: In this study, we evaluated anonymous data from 139931 patients aged 1-100 years with multiple trauma in the TraumaRegister DGU® of the German Society for Trauma Surgery from 2007 to 2017. Patients with hand and forearm injuries … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…Fractures of forearm and hand in patients with multiple trauma can occur in 36% of cases [ 12 ]. In our original study population, we determined a prevalence of 12.1% for late diagnosis of fractures of forearm and hand [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fractures of forearm and hand in patients with multiple trauma can occur in 36% of cases [ 12 ]. In our original study population, we determined a prevalence of 12.1% for late diagnosis of fractures of forearm and hand [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Distal intra-articular radius fractures occurred most frequently (26.1%). In recent imaging and register studies incidences varied between 15.5% for fractures of hand and forearm in ventilated patients and 36.1% for osseous and soft-tissue injuries [ 12 , 13 ]. Ferree et al reported an incidence of 3.5% for fractures and dislocations of the hand with a predisposition for fractures of the metacarpal bones (48%) [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The selection of the screening cohort was based on the German S3 guideline for the treatment of polytrauma and the severely injured [ 20 ] and consisted of a typical, real-life cohort of all trauma patients who were examined via WBCT during the study period. An alternate approach through patient records and data bases, including patients based on the severity of injuries, should increase the pretest probability of the examination results [ 12 ]. For the same reason, the incidence of osseous wrist and hand fractures might be higher in a cohort of ventilated patients, which have potentially suffered greater severity of injuries or high-impact trauma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Gaheer and Ferdinand [26] reported about one case with a third metacarpal base fracture associated with primarily missed dislocations of the CMCJ IV and V, Brinkman et al [27] observed one case with CMCJ II-V dislocations associated with a concurrent fracture of the hamate bone, and Feder et al [28] reported about one case with a 180° in situ dislocation of the trapezoid bone associated with concomitant CMCJ II and III dislocations. Noted was well that a newest study including 139,931 polytraumatized patients revealed that the relative portion of primarily missed hand injuries is 6.6% (excluding distal radius fractures), and 11.2% of these patients sustained carpal fractures/ dislocations [29].…”
Section: Discussionmentioning
confidence: 99%